The portrait of neem leaves-based high performance wound healing activity on zebrafish - Nour Athiroh; Ari Hayati; Istirochah Pudjiwati; Ahmad Taufiq; Nurul Jadid Mubarakati (The East Java Biological Society, 2021)
This study was designed to evaluate the role of sliced and dropping models of neem leaves (Azadirachta indica) and environmental factors on zebrafish wound shrinkage. This study employed two treatment models: neem leaf slices and drops model. The treatment in the neem leaf slice model was the control group (fish was injured without neem leaf slices treatment, and G1-G3 of each fish was injured at 0.3 cm + 0.5, 1, and 2 g. Treatment in the neem leaf drop model was control group (fish was injured without neem leaves drops, and G1-G3 of each fish was injured at 0.3 cm + 1, 2, 4 drops. Findings suggest that there is a significant difference between the control group by treating G1, G2, and G3 on the shrinkage of zebrafish wound area both in the neem leaf slice and drop models, but G1 was not significantly different from G2 and G3, as well as G2 and G3 both in the neem leaf slice and drop model. Neem leaves contain nutrients that play a vital role in the formation of collagen and the formation of new capillaries to help speed up the wound healing process. The healing process involves the dynamic interaction of physiological factors.